Fiber and microelements content in various types of wheat bread - Redžepović-Đorđević Azra; Dodevska Margarita; Jovetić Milica; Ačanski Marijana (Journal of the Serbian Chemical Society)
Various types of wheat bread are present in the Serbian market: white, brown, whole-wheat, wheat/rye, buckwheat/wheat, half-white and corn/ /wheat bread. This research included the quantification of the content of total fiber, fiber fractions, and microelements (manganese, copper, iron and zinc) in order to check whether the breads on the market contain the amounts that are proven beneficial for health. The aim was also to determine the contribution of these nutrients through the consumption of bread to the recommended daily intake. The results show that the bread from the Serbian market contains a large amount of arabinoxylan (1.2–2.6 g 100 g-1) and that wheat/rye, brown and whole wheat bread are sources of dietary fiber (4.0–4.6 g 100 g-1). Also, an important result is that all types of bread except white, contain more than 15 % of dietary reference values for copper and manganese. The intake of total fiber (+ 100 %), arabinoxylan (+ 117 %), copper (+ 118 %), and manganese (+ 85 %) increases by replacing white bread with whole wheat bread, therefore it is of great interest to raise awareness among consumers about the beneficial foods that should be included in the diet. Methods applied in this research showed acceptable precision and accuracy and also proved to be quite simple for routine analysis work.